Respuesta :
Answer: The area is: "(x² + x + 3) (x² + 2x + 4)" square units ;
or, write as:
_____________________________________________________
" x⁴ + 3x³ + 9x² + 10x + 12" square units.
_____________________________________________________
Explanation:
_____________________________________
Area of a triangle = ½ * (base length) * (height) ; or:
A = ½ * b * h ; Plug in values given:
A = ½ * (x² + 2x + 4) * (2x² + 2x + 6) ;
↔ A = ½ * (2x² + 2x + 6) * (x² + 2x + 4) ;
_______________________________________
Note: ½ * (2x² + 2x + 6) = (2x² + 2x + 6) / 2 =
x² + x + 3 ;
_________________________________________
Rewrite:
_________________________________________
A = "(x² + x + 3) (x² + 2x + 4)" square units ; or expand further and solve:
__________________________________________
x² * x² = x⁽²⁺²⁾ = x⁴ ;
_____________________
x² * 2x = 2x³ ;
____________________
x² * 4 = 4x² ;
_____________________
x * x² = x¹ * x² = x⁽¹⁺²⁾ = x³ ;
______________
x * 2x = 2x² ;
_____________
x * 4 = 4x ;
_____________
3 * x² = 3x² ;
_____________
3 * 2x = 6x ;
__________
3 * 4 = 12
__________
So, we have: x⁴ + 2x³ + 4x² + x³ + 2x² + 4x + 3x² + 6x + 12 ;
→ Combine the "like terms" ;
_______________________________
+2x³ + x³ = 3x³
+4x² + 2x² + 3x² = 9x²
+4x + 6x = 10x
______________________________________________
And we have: " x⁴ + 3x³ + 9x² + 10x + 12" square units .
_________________________________________________
or, write as:
_____________________________________________________
" x⁴ + 3x³ + 9x² + 10x + 12" square units.
_____________________________________________________
Explanation:
_____________________________________
Area of a triangle = ½ * (base length) * (height) ; or:
A = ½ * b * h ; Plug in values given:
A = ½ * (x² + 2x + 4) * (2x² + 2x + 6) ;
↔ A = ½ * (2x² + 2x + 6) * (x² + 2x + 4) ;
_______________________________________
Note: ½ * (2x² + 2x + 6) = (2x² + 2x + 6) / 2 =
x² + x + 3 ;
_________________________________________
Rewrite:
_________________________________________
A = "(x² + x + 3) (x² + 2x + 4)" square units ; or expand further and solve:
__________________________________________
x² * x² = x⁽²⁺²⁾ = x⁴ ;
_____________________
x² * 2x = 2x³ ;
____________________
x² * 4 = 4x² ;
_____________________
x * x² = x¹ * x² = x⁽¹⁺²⁾ = x³ ;
______________
x * 2x = 2x² ;
_____________
x * 4 = 4x ;
_____________
3 * x² = 3x² ;
_____________
3 * 2x = 6x ;
__________
3 * 4 = 12
__________
So, we have: x⁴ + 2x³ + 4x² + x³ + 2x² + 4x + 3x² + 6x + 12 ;
→ Combine the "like terms" ;
_______________________________
+2x³ + x³ = 3x³
+4x² + 2x² + 3x² = 9x²
+4x + 6x = 10x
______________________________________________
And we have: " x⁴ + 3x³ + 9x² + 10x + 12" square units .
_________________________________________________